VULNERABILITY OF POTATO WHITE GRUB TO ENTOMOGENOUS FUNGI AND NEMATODES - Chandel, R S.; Chandla, V. K.; Dhiman, K. R. (Potato Journal, 2013)
The efficacy of entomogenous fungi and nematode in controlling Brahmina coriacaea (Hope) grubs was determined in pot experiments and under field conditions. B. coriacea grubs had medium to low susceptibility to fungi, Metarrhizium anisopliae and Beauveria bassiana in laboratory. Under field condition, both these fungi, didn’t provide satisfactory control of potato white grubs. B. coriacea grubs were highly susceptible to nematode Heterorhabditis indica. In laboratory assays, H. indica caused 100 and 80.46% mortality of second and third instar grubs, respectively. The application of H. indica did reduce the damage by grubs to potato tubers. Lesser number of grubs were observed in nematode treated plots and white grub infestation was 8.13% as compared to 11.28% in untreated plots.